Fault-tolerant supervisory control in Discrete Event Systems: An implementation proposal Controle Supervisório Tolerante a Falhas em SEDs: uma proposta de implementação - Bellarmino L.* (2023)
© 2023 IEEE.This work presents a proposal for implementing fault-tolerant distributed supervisory control for Discrete Event Systems. The supervisor localization approach is adopted to obtain the control structure and the obtained supervisors are implemented in different Function Blocks, executed in a Programmable Logic Controller. The fault tolerance was obtained through the use of reconfiguration block between the controller and the plant. The proposal is applied in a case study developed on a virtual plant of the Factory IO software.